RAD-UCD Implementation in Project Management Information System - Anugrah, Indra Gita; Witra, Widyasari Puspa Permata; Nuha, Sukma Uli; Wibowo, Nugroho Setyo; Utomo, Denny Trias (Journal of Development Research, 2024)
This study discusses the implementation of Rapid Application Development (RAD) and User-Centered Design (UCD) methods in developing project management information systems for small and medium-scale projects. Using interviews and direct trials by project managers, project team members, and clients, this study aims to understand the extent to which these two methods can improve development efficiency and user satisfaction. The results show that the RAD method accelerates the development process through flexible iterations, while UCD ensures that the resulting system is in accordance with user needs. Project managers reported increased transparency in monitoring progress, team members appreciated features that supported coordination, and clients felt more connected to project developments in real time. The combined implementation of RAD and UCD proved effective in creating a responsive, efficient, and user-friendly project management system to meet the needs of small and medium projects.